Associations between the combined physical activity environment, socioeconomic status, and obesity: a cross-sectional study. (May 2018) - Hobbs, M; Griffiths, C; Green, MA; Jordan, H; Saunders, J; McKenna, J
Aims: This study investigates associations between the combined physical activity environment and obesity and explores any sub-group effects by individual-level socioeconomic status. Methods: In a large cross-sectional cohort ( n  = 22, 889) from the Yorkshire Health Study, body mass index was calculated using self-reported height and weight and obesity was defined as a body mass index ≥ 30. The physical activity environment was split into 'unfavourable physical activity', 'moderately favourable physical activity' and 'favourable physical activity' environments. This was based on the count of parks and physical activity facilities within a 2 km radial buffer centred on home addresses. A favourable physical activity environment was defined as having ≥1 physical activity facility and ≥1 park, unfavourable as having no physical activity facility and park and any other combinations defined as moderately favourable. Logistic regression (odds ratios) identified associations with obesity. Results: Relative to 'unfavourable physical activity environments', individuals within favourable physical activity environments were less likely to be obese (odds ratio = 0.90; 95% confidence interval = 0.82–0.97), and there was no effect for moderately favourable environment. Furthermore, once stratified by education level, this relationship was only present for those of higher education. Conclusion: Our findings provide novel UK evidence and is one of the first papers internationally that highlights the importance of considering the interplay of individual-level socioeconomic factors when investigating associations between the physical activity environment and obesity.